2016
DOI: 10.1093/ecco-jcc/jjw049
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative Colitis Remission Status After Induction With Mesalazine Predicts Maintenance Outcomes: the MOMENTUM Trial

Abstract: Background and Aims:This study assessed the efficacy of maintenance treatment with multimatrix mesalazine following achievement of complete or partial remission after induction treatment with high-dose multimatrix mesalazine.Methods:In this phase 3b/4, open-label, multicentre, prospective, single-arm study, patients with mild-to-moderate ulcerative colitis were treated with multimatrix mesalazine 4.8g/day once daily for 8 weeks [induction phase]. At Week 8, those who achieved complete or partial remission, bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…Recently, the importance of mucosal healing has been emphasized. It has been reported that remission of UC is maintained for a longer period when the mucosal healing is achieved by induction therapy 121314. Furthermore, in the present study, the difference in the change in the rectal bleeding score, the main symptom of UC, was statistically significant between the 2 groups at week 2, as well as at subsequent visits.…”
Section: Discussionsupporting
confidence: 59%
“…Recently, the importance of mucosal healing has been emphasized. It has been reported that remission of UC is maintained for a longer period when the mucosal healing is achieved by induction therapy 121314. Furthermore, in the present study, the difference in the change in the rectal bleeding score, the main symptom of UC, was statistically significant between the 2 groups at week 2, as well as at subsequent visits.…”
Section: Discussionsupporting
confidence: 59%
“…The proportion of patients without rectal bleeding for 48 weeks was 76.9% in the pH-dependent delayed-release mesalazine 2.4 g/day TID group and 69.2% in the controlled-release mesalazine 2.25 g/day TID group. In another phase IIIb/IV open-label study of multimatrix mesalazine (the MOMENTUM trial), rectal bleeding was also investigated as one of the secondary endpoints during maintenance treatment with multimatrix mesalazine 2.4 g/day 14. The proportion of patients who maintained a rectal bleeding score of 0 for 12 months was 65.4% in patients with complete remission (modified UC-DAI score ≤1 with a score of 0 for both rectal bleeding and stool frequency, and ≥1-point reduction in endoscopy score from baseline) after induction treatment with multimatrix mesalazine 4.8 g/day for 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term continuous treatment with high-dose MSZ (4.0 g/day) was more effective (relapsefree rate higher and mean time to relapse longer) than short-term treatment for maintenance of remission in UC patients (23). In a recent study (MOMENTUM Trial), patients achieving complete remission with a multimatrix MSZ 4.8 g/day once daily for eight weeks and then beginning dose reduction were more likely to remain in remission at month 12 than patients who began maintenance in partial remission (24). In our study, patients with flare-ups in the previous year more frequently maintained the higher dose of MSZ compared with patients without recent flare-ups (51% vs 27%, respectively).…”
Section: Discussionmentioning
confidence: 99%